Cell Type-Specific Genetic Manipulation and Impaired Circadian Rhythms in ViptTA Knock-In Mice - Peng, Yubo; Tsuno, Yusuke; Matsui, Ayako; Hiraoka, Yuichi; Tanaka, Kohichi; Horike, Shin-ichi; Daikoku, Takiko; Mieda, Michihiro (Frontiers in Physiology, 2022)
The suprachiasmatic nucleus (SCN), the central circadian clock in mammals, is a neural network consisting of various types of GABAergic neurons, which can be differentiated by the co-expression of specific peptides such as vasoactive intestinal peptide (VIP) and arginine vasopressin (AVP). VIP has been considered as a critical factor for the circadian rhythmicity and synchronization of individual SCN neurons. However, the precise mechanisms of how VIP neurons regulate SCN circuits remain incompletely understood. Here, we generated Vip-tTA knock-in mice that express tetracycline transactivator (tTA) specifically in VIP neurons by inserting tTA sequence at the start codon of Vip gene. The specific and efficient expression of tTA in VIP neurons was verified using EGFP reporter mice. In addition, combined with Avp-Cre mice, Vip-tTA mice enabled us to simultaneously apply different genetic manipulations to VIP and AVP neurons in the SCN. Immunostaining showed that VIP is expressed at a slightly reduced level in heterozygous Vip-tTA mice but is completely absent in homozygous mice. Consistently, homozygous Vip-tTA mice showed impaired circadian behavioral rhythms similar to those of Vip knockout mice, such as attenuated rhythmicity and shortened circadian period. In contrast, heterozygous mice demonstrated normal circadian behavioral rhythms comparable to wild-type mice. These data suggest that Vip-tTA mice are a valuable genetic tool to express exogenous genes specifically in VIP neurons in both normal and VIP-deficient mice, facilitating the study of VIP neuronal roles in the SCN neural network.